1994
DOI: 10.1177/0022427894031002007
|View full text |Cite
|
Sign up to set email alerts
|

Racial Prejudice and Support for the Death Penalty by Whites

Abstract: Although many studies have found that Whites are more likely than Blacks to support the death penalty, little research has investigated the reasons for this difference. Using data from the 1990 General Social Survey, this study finds that White support for capital punishment is associated with prejudice against Blacks. Final remarks discuss the implications of the results for legislative and judicial decisions regarding capital punishment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
163
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(177 citation statements)
references
References 24 publications
13
163
1
Order By: Relevance
“…A legal death penalty is likely in states with the most black residents (Jacobs and Carmichael 2002). Findings that public support for capital punishment is associated with black presence and racial prejudice (Barkan and Cohn 1994;Soss, Langbein, and Metelko 2003) This relationship may not be linear (Blalock 1967). Theory suggests that whites will make greater demands for punitive measures after expansions in black presence.…”
Section: MI In No Ormentioning
confidence: 99%
“…A legal death penalty is likely in states with the most black residents (Jacobs and Carmichael 2002). Findings that public support for capital punishment is associated with black presence and racial prejudice (Barkan and Cohn 1994;Soss, Langbein, and Metelko 2003) This relationship may not be linear (Blalock 1967). Theory suggests that whites will make greater demands for punitive measures after expansions in black presence.…”
Section: MI In No Ormentioning
confidence: 99%
“…Using data from the General Social Survey, Barkan and Cohn (1994) examined the answers of White respondents to questions regarding their fear of crime, dislike of Blacks, and racial stereotyping. They found that support for the death penalty was positively associated with racial stereotyping and hostility towards Blacks.…”
Section: Racial Bias In the Penalty Phase Of Capital Trialsmentioning
confidence: 99%
“…Several authors have postulated that racial prejudice is a likely predictor of racial disparities in the application of death sentences (Cohn et al, 1991;Ford, 1997). Many studies have found that the greater the racial prejudice among Whites, the greater the support for the death penalty (Aguirre and Baker, 1993;Barkan and Cohn, 1994;Ford, 1997). However, the reason why racial prejudice is significantly related to support for the death penalty (SDP) still remains relatively unclear.…”
Section: Introductionmentioning
confidence: 99%